Frequency-independent equivalent-circuit model for on-chip spiral inductors. - Yu Cao
A wide-band physical and scalable 2-Π equivalent circuit model for on-chip spiral inductors is developed. Based on physical derivation and circuit theory, closed-form formulas are generated to calculate the RLC circuit elements directly from the inductor layout. The 2-Π model accurately captures R(f) and L(f) characteristics beyond the self-resonant frequency. Using frequency-independent RLC elements, this new model is fully compatible with both ac and transient analysis. Verification with measurement data from a SiGe process demonstrates accurate performance prediction and excellent scalability for a wide range of inductor configurations.
Keywords: AC analysis; SiGe; SiGe process; Frequency-independent RLC elements; On-chip spiral inductor; Self-resonant frequency; Transient analysis; 2-Π equivalent circuit model